PERSONALITY TYPE TENDENCY TOWARD STUDENTS’ SPEAKING ANXIETY - Balqis Husain; Megawati Basri; Jasmal Martora; Amrin Sibua; Irwan Gogasa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2020)
Pupils at the eleventh grade of SMA N 1 Morotai have different personality types, most of whom often feel anxious when speaking. This research is aimed at finding out whether or not introvert and extrovert personality types have correlation with pupils’ level of anxiety in speaking English. This research is quantitative in nature, using causal- correlative method. The population of the research was all pupils in the seventh grade of SMA N 1 Pulau Morotai. The total number of population was 140 pupils but 105 pupils were selected to participate as the sample of this research. In choosing the sample, the researchers applied Krejchie- Morgan’s table with 5% error rate. In terms of data analysis, the researchers took two instrument tests; namely personality test and level of anxiety during English speaking test. To know the personality types of the pupils, the researchers utilized Eysenck Personality Inventory (EPI) test. Questionnaire of Foreign Language Classroom Anxiety Scale (FLCAS), on the other hand, was used to know the students’ level of anxiety. Result of hypothesis testing analysis shows that there was no significant difference in the level of speaking anxiety between the pupils who have introvert and extrovert personality types. The value of sig 0.264 was found to be higher than α = 0.05.